Respuesta :
- D:2x²-3x-8
Answer:
Solution given:
f(x)=2x²-5
g(x)=3x+3
now
(f-g) (x)=?
we have
(f-g)(x)=f(x)-g(x)
- =2x²-5-(3x+3)
- =2x²-5-3x-3
- adding or subtracting common term
- =2x²-3x-8
Answer:
[tex]2x^{2} - 3x - 8[/tex]
Step-by-step explanation:
Step 1: Define what (f-g)(x) means
(f-g)(x) means that we have two different functions, f(x) and g(x). (f-g)(x) is a shorter way of writing f(x) - g(x). Therefore you just plug in the equations and combine like terms.
Step 2: Find (f-g)(x)
[tex]f(x) = 2x^{2} - 5[/tex]
[tex]g(x) = 3x + 3[/tex]
[tex](f-g)(x) = 2x^{2} - 5 - (3x + 3)[/tex]
[tex](f-g)(x) = 2x^{2} - 5 - 3x - 3[/tex]
[tex](f-g)(x) = 2x^{2} - 3x - 8[/tex]
Answer: [tex]2x^{2} - 3x - 8[/tex]